IMPLEMENTASI MODEL PEMBELAJARAN DRTA (DIRECTED READING-THINKING ACTIVITY) SEBAGAI INOVASI PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DI SEKOLAH DASAR - Handayani, Sri; Nugrahani, Farida; Suwarto, Suwarto (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the implementation of the DRTA (Directed Reading-Thinking Activity) model in learning Indonesian Language and Literature in class V SDN Bakalan 03, Polokarto, Sukoharjo. Descriptive qualitative research with a case study design. Data were collected through in-depth interviews, observation, and documentation, and analysed using data reduction, data presentation, and conclusion drawing/verification, while data validation was obtained using data triangulation and theory triangulation techniques. The results showed that the implementation of the DRTA (Directed Reading-Thinking Activity) model was very good. The research conclusions include good implementation, supporting factors such as the completeness of facilities and student motivation, inhibiting factors such as lack of student understanding, and teacher solutions tailored to obstacles.